Municipal Finance in Poland, the Slovak Republic, the Czech Republic and Hungary: Problems and Prospects - Chang Woon Nam; Rüdiger Parsche (European Regional Science Association (ERSA), 2001)
The recent process of political and economic transformation in eastern European countries has not only contributed to the decentralisation of political structure but also significantly enhanced the fiscal autonomy of municipalities belonging to these countries. Although the degree of self-governing abilitiy of municipalities seems to vary from one country to another, many similar types of public activities have recently been assigned to local governments, and some taxes were also declared to be the so-called local taxes. To be sure, this type of fiscal decentralisation has caused some additional problems, particularly for safeguarding the quality of publicly provided goods and services and for coordinating intergovernmental fiscal transfers between the central and local governments in an efficient way. For instance, some criticise that a large number of small-sized municipalities in the transition economies have suffered from the financial bottleneck and have not been able to receive financial support from the central government that was necessary for their economic development. However, such a fiscal devolution trend appears to continue in these countries, in parallel to the ongoing democratisation and decentralisation. This paper primarily deals with crucial issues surrounding the impact of national fiscal policy and the regulatory framework on local government's expenditure behaviour and their ablility to mobilise necessary revenues (i.e. tax income, grants and municipal borrowings) under the particular consideration of the institutional cooperation with the central government and of the (still existing) less-well developed financial market in Poland, the Slovak Republic, the Czech Republic and Hungary.
Keywords: 330